EXPERIMENTAL INVESTIGATION OF TIO₂-MODIFIED CONCRETE: MICROSTRUCTURAL BEHAVIOR, MECHANICAL PERFORMANCE, DURABILITY CHARACTERISTICS, AND ENVIRONMENTAL IMPLICATIONS - Shreeshail Heggond; Satish Tasildhar (International Educational Journal of Science and Engineering, 2026)
Titanium dioxide (TiO₂) has attracted considerable scholarly and industrial attention as a functional additive for cementitious composites, owing to its photocatalytic activity, chemical inertness, and the potential it holds for improving both the engineering performance and environmental credentials of concrete structures. This review synthesizes and critically evaluates experimental evidence from more than three decades of research concerning the incorporation of TiO₂ into ordinary Portland cement (OPC)-based systems, encompassing anatase and rutile polymorphs at dosages typically ranging from 1% to 10% by mass of binder. The paper examines the microstructural modifications induced by TiO₂ addition, including pozzolanic reactivity, pore size refinement, and interfacial transition zone (ITZ) densification. Mechanical performance data drawn from diverse studies consistently demonstrate compressive strength gains of 10–25% at optimal dosages (typically 2–5 wt.%), alongside improvements in tensile and flexural capacity. Durability assessments reveal reduced water absorption, lower chloride penetration depth, and enhanced resistance to sulfate attack and carbonation. The photocatalytic properties of TiO₂-modified concrete are evaluated in the context of air purification, de-pollution of nitrogen oxides (NOx) and volatile organic compounds, and self-cleaning surface behavior. Contradictory findings in the literature are critically addressed, particularly concerning the effects of high TiO₂ dosages and particle size on workability and long-term hydration kinetics. Environmental implications, including embodied energy trade-offs, lifecycle considerations, and urban heat island mitigation, are also discussed. Future research directions and practical challenges associated with large-scale deployment are identified, providing a nuanced foundation for material scientists, structural engineers, and sustainability researchers.